What is Rubbish?
An interview with Tim, a British hobo in one of the parks in Amsterdam. The director prompts Tim to reach into the deep recesses of his pockets and to empty his bags for him, revealing an odd inventory of odds and ends that Tim collected in the street - lighters, McDonald's tokens, invalid telephone cards, penknives, Chinese lucky charms, food past its expiry date, change, pencils, etc., all of which takes the concept of rubbish to a whole new level. "You keep all that stuff in your pockets?" - "Yes, why would I throw that out, what is rubbish?"